Specifying the sources of misperceptions of peer deviance: a tale of two levels - Boman, John H. (Criminal justice and behavior, 2014)
?Peer deviance? is normally measured through one?s perceptions of the deviant behavior of friends. However, recent research suggests that peer deviance perceptions may be inaccurate and unreflective of a peer?s actual deviance. Using dyadic data, the current study addresses the potential for three distinct sources of misperceptions of peer deviance stemming from (a) the actor who generates the perception, (b) the friend about whose deviance is perceived, and (c) the friendship between the actor and the friend. Using multilevel regression alongside analyses of variance (ANOVAs), results demonstrate that misperceptions, overperceptions, and underperceptions of peer deviance occur frequently and systematically covary with the deviant behavior of the perceiver, the friend, and the total amount of deviance within the friendship.